Substitution on noncash payment instruments for cash in Europe - Jussi Snellman; Jukka Vesala; David Humphrey (Bank of Finland, 2000)
The substitution of noncash (check, giro, and credit and debit card) payments for cash transactions is difficult to gauge because there are no data series on the actual value or volume of cash transactions in any country.However, determining the degree of cash substitution is important because it will negatively affect government seigniorage revenue and, if cash use falls fast enough, may require tax revenues to redeem excess currency holdings.We utilise a novel method for approximating the volume of cash transactions using public information on currency stocks and noncash payments.Applying this method, we estimate how cash has been substituted by other payment instruments in 10 European countries.We also provide a forecast of future cash use by country.We find that the trend in cash substitution across countries is quite similar.However, the countries themselves are at significantly different stages of this substitution process.The spread of debit and credit card payments has been the key factor behind the substitution away from cash as use of e-cash innovation is still in its infancy.Country-specific differences in the substitution process are largely explained by differences in the level of implementation of each country's card payment technology.
URN:NBN:fi:bof-20140807614
Keywords: 330